1991
DOI: 10.1111/j.1939-1676.1991.tb00954.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Taurine Concentrations and M‐mode Echocardiographic Measures in Healthy Cats and in Cats with Dilated Cardiomyopathy

Abstract: M-mode echocardiography was completed and plasma taurine concentrations were determined in 79 healthy cats and 77 cats with dilated cardiomyopathy (DCM). In healthy cats, a relationship was not observed between plasma taurine concentrations and any M-mode echocardiographic measurement. End-systolic and end-diastolic cardiac chamber dimensions were larger; wall thickness measures were smaller; and calculations of fractional shortening were less in cats with DCM than in healthy cats. Plasma taurine concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
65
2
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 18 publications
6
65
2
1
Order By: Relevance
“…The mean LVW values for the geriatric cats in the present study were very similar to those previously reported for normal cats. 25 Although there was a tendency for the SHT group to have LVH, SHT could not be conclusively excluded based on LVW thickness.…”
Section: Discussionmentioning
confidence: 99%
“…The mean LVW values for the geriatric cats in the present study were very similar to those previously reported for normal cats. 25 Although there was a tendency for the SHT group to have LVH, SHT could not be conclusively excluded based on LVW thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Portanto, pouca relação existe entre gatos domésticos não anestesiados, estudados por Jacobs e Knight (1985) e por Sisson et al (1991), e os animais da espécie estudada, que sofreram contenção química com a associação de xilazina e quetamina.…”
Section: Methodsunclassified
“…The average age of affected cats is 9 years [1,2]. Siamese and Abyssinians seem to be predisposed [1,36]. …”
Section: Dilated Cardiomyopathiesmentioning
confidence: 99%